Knowledge of HIV Status Is Associated With a Decrease in the Severity of Depressive Symptoms Among Female Sex Workers in Uganda and Zambia. (1st January 2020) - Ortblad, Katrina F.; Musoke, Daniel Kibuuka; Chanda, Michael M.; Ngabirano, Thomson; Velloza, Jennifer; Haberer, Jessica E.; McConnell, Margaret; Oldenburg, Catherine E.; Bärnighausen, Till
Abstract : Background: Knowledge of HIV-positive status may result in depressive symptoms, which may be a concern to scaling novel HIV testing interventions that move testing outside the health system and away from counselor support. Setting: Uganda and Zambia. Methods: We used longitudinal data from 2 female sex worker (FSW) cohorts in Uganda (n = 960) and Zambia (n = 965). Over 4 months, participants had ample opportunity to HIV testing using standard-of-care services or self-tests. At baseline and 4 months, we measured participants' perceived knowledge of HIV status, severity of depressive symptoms (continuous PHQ-9 scale, 0–27 points), and prevalence of likely depression (PHQ-9 scores ≥10). We estimated associations using individual fixed-effects estimation. Results: Compared with unknown HIV status, knowledge of HIV-negative status was significantly associated with a decrease in depressive symptoms of 1.06 points in Uganda (95% CI −1.79 to −0.34) and 1.68 points in Zambia (95% CI −2.70 to −0.62). Knowledge of HIV-positive status was significantly associated with a decrease in depressive symptoms of 1.01 points in Uganda (95% CI −1.82 to −0.20) and 1.98 points in Zambia (95% CI −3.09 to −0.88). The prevalence of likely depression was not associated with knowledge of HIV status in Uganda but was associated with a 14.1% decrease with knowledge of HIV-negative status (95% CI −22.1% to −6.0%) and a 14.3% decrease with knowledge of HIV-positive status (95% CI −23.9% to −4.5%) in Zambia. Conclusions: Knowledge of HIV status, be it positive or negative, was significantly associated with a decrease in depressive symptoms in 2 FSW populations. The expansion of HIV testing programs may have mental health benefits for FSWs. Abstract : Supplemental Digital Content is Available in the Text.